AB0250 The adipose tissue as predictive factor of disease activity in rheumatoid arthritis patients: evaluation of body fat composition by bioelectrical impedance analysis and ultrasonography. (15th June 2017) - Anelli, MG; Rotondo, C; Fanizzi, R; Magazzino, O; Giannotta, M; Giannini, M; Lorusso, O; Praino, E; Viggiani, MT; Cacciapaglia, F; Barone, M; Lapadula, G; et al.
Abstract : Background: Adipose tissue (AT) is an endocrine organ able to secrete the "adipokine" molecules that contribute to the low-grade inflammatory state in obese subjects and to the local inflammation that affects joints and bone (1, 2). High-grade inflammation, in course of RA, leads to an altered body composition (3, 4), characterized by the increasing of fat mass and the decreasing of lean mass, mostly not associated to body mass index (BMI) variations (3, 5). The BMI is not able to differentiate visceral (VTH) and subcutaneous (STH) fat tissue and to distinguish between muscle mass and fat mass body composition (BC) (6, 7). Alternative methods proposed for assessment of visceral fat deposition, are bioelectrical impedance analysis (BIA) and ultrasonography (US). Objectives: The aim of the study is to investigate if BC, assessed by BIA and US, correlates with disease activity (assessed by the Disease Activity Score using 28 joint counts – DAS28) and affects the response to the therapy (DAS 28 variation from first evaluation). Methods: 87 consecutive RA patients (pts) (72 women and 15 men; aged 52.4±13.2 years; disease duration of 10.7±8.6 years), treated with DMARDs and/or biologics (bDMARDs), were recruited during their regular visit. The inclusion criteria were the 1987 American College of Rheumatology (ACR) or ACR/EULAR 2010 classification criteria. The pts underwent to anthropometric measures (BMI); abdominal US to assess STH and VTH and derived computing of peritoneal circumference (PC); and BIA to the indices of body composition (fat-free mass index (FFMI) and fat mass index (FMI). Results: We observed increasing values of BMI, FMI, VTH (fig. 1 ) and CP with the worsening of disease activity phases, evaluated by DAS 28. In particular, pts with DAS28≥5.1 had highest BMI (30, 9±2; p=0, 036), FMI (11, 5±1, 6; p=0, 05), CP (92, 7±12, 5 cm; p=0, 035) and VTH (24, 8±5, 8 mm; p=0, 046) than pts in less severe disease activity. By linear regression analysis the predictor of higher DAS28 is the BMI (p=0, 028). As regard the drug response, the predictors of DAS 28 improvement are higher FFMI (p=0, 044) and lower BMI (p=0, 015), independently by bDMARDs or DMARDs treatment. A trend to higher FMI and US AT measures was observed in female with high disease activity, in particular in menopause pts. Conclusions: An altered fat distribution is observed in active RA phases; in particular, the FMI increasing is attributable just to visceral AT (VTH and CP). An inflammatory hyperactivity of visceral adiposity could be supposed in RA. The body composition, in addition to BMI, seems to predict the disease activity and drug response in RA patients. The evaluation of VTH by US could be useful to not overestimate the disease activity; instead the BIA could be a useful tool to support the clinicians in a more aggressive treatment management. References: Nat Clin Pract Rheumatol 2007; 3(12):716–24. J Mol Endocrinol 2009; 43(1):11–8. Mediators Inflamm 2013; 2013:710928. Arthritis Care Res (Hoboken) 2012; 64(10):1471–9. Nat Rev Rheumatol 2010; 6(8):445–51. Curr Opin Clin Nutr Metab Care 2003; 6(4):387–93. Ann Rheum Dis 2007; 66(10):1316–21. Disclosure of Interest: None declared